Preeclampsia and the Long-Term Risk of Ischemic and Hemorrhagic Stroke: A Systematic Review and Analysis of Population-Based Studies - Andre Gunawan Halim; Harry Verial L Simatupang (International Medical Journal Corp. Ltd, 2025)
Introduction: Preeclampsia, a multi-system hypertensive disorder of pregnancy, is increasingly recognized as a potent, sex-specific risk factor for future cardiovascular disease. However, a comprehensive synthesis of the long-term risk for specific stroke subtypes remains a critical need for guiding clinical practice. This systematic review aims to quantify the association between a history of preeclampsia and the long-term risk of ischemic and hemorrhagic stroke, based on evidence from large-scale, population-based studies. Methods: A systematic search of PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library was conducted for population-based cohort and case-control studies that evaluated the association between preeclampsia and the long-term risk of ischemic and/or hemorrhagic stroke. The review was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data on study design, population characteristics, follow-up duration, and quantitative risk estimates (Hazard Ratios, Odds Ratios, or Relative Risks with 95% Confidence Intervals) were extracted. The methodological quality and risk of bias of included studies were assessed using the Risk Of Bias In Non-randomized Studies - of Interventions (ROBINS-I) tool. Results: Seventeen population-based studies, encompassing over 10 million women, met the inclusion criteria. The evidence consistently demonstrated a statistically significant association between a history of preeclampsia and an increased risk of future stroke. Women with a history of preeclampsia had an approximately two-fold increased risk of overall stroke compared to women with normotensive pregnancies. The risk was significantly elevated for both ischemic stroke (pooled risk estimates ranging from 1.8 to 4.1) and hemorrhagic stroke (pooled risk estimates ranging from 2.2 to 4.1), with several studies indicating a proportionally higher risk for hemorrhagic events. The risk was magnified in cases of severe, early-onset, or recurrent preeclampsia, indicating a dose-response relationship. Temporal analyses revealed distinct risk trajectories: the risk of ischemic stroke peaked within the first 5 years postpartum, whereas the risk of hemorrhagic stroke appeared to increase more gradually and persist for decades. Discussion: The robust epidemiological association is supported by strong biological plausibility. Preeclampsia induces a state of systemic endothelial dysfunction, inflammation, and hypercoagulability, driven by placental anti-angiogenic factors. This vascular insult may not fully resolve postpartum, leading to persistent subclinical damage and accelerating the development of chronic hypertension and other cardiovascular risk factors. The early peak in ischemic stroke risk may reflect the subacute prothrombotic state, while the later, sustained risk of hemorrhagic stroke is likely a consequence of long-term hypertensive vasculopathy. Conclusion: A history of preeclampsia is a significant and independent risk factor for both ischemic and hemorrhagic stroke, conferring a lifelong burden of increased cerebrovascular risk. Obstetric history must be integrated into routine cardiovascular risk assessment for women. Postpartum surveillance, focused on aggressive blood pressure management and lifestyle modification, is imperative for women with a history of preeclampsia to mitigate their long-term risk of stroke.